Women with PCOS who undergo IVF: a comprehensive review of therapeutic strategies for successful outcomes - Alexander M. Kotlyar; David B. Seifer (BMC, 2023)
Abstract Polycystic ovarian syndrome (PCOS) is a widespread syndrome that poses unique challenges and constraints to the field of assisted reproductive technology. This condition is the most common cause of anovulation among infertile couples. Debate exists over the best therapeutic course of action when patients with PCOS proceed to IVF. In this review, we evaluate the best-performing and safest methods of IVF preparation, ovarian stimulation, trigger method for maturation of stimulated egg growth, and planning for embryo transfer. Pre-IVF considerations include being aware of individual AMH and vitamin D levels as well as BMI prior to selecting an ovarian stimulation protocol. Numerous supplements such as myo-inositol complement the benefits of lifestyle change and may enhance IVF performance including oocyte yield and pregnancy rate. Concerning stimulation protocols, antagonist cycles with the judicious use of GnRH agonist trigger, pre-treatment with metformin and vitamin D repletion may help mitigate the accompanied risk of ovarian hyperstimulation syndrome (OHSS). Following ovarian stimulation, PCOS patients typically undergo programmed frozen embryo transfer (FET) cycles which are more conducive for women with irregular cycles, but likely carry a higher risk of hypertensive disorders of pregnancy. However, newer stimulated FET protocols using Letrozole may offer improved outcomes. Overall, patients with PCOS require careful individual tailoring of their IVF cycle to achieve optimal results.